UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH - BERTHA DIMARA (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
Efforts to increase Teacher Professional Competence through the Implementation of Principal Academic Supervision have been carried out at SD Inpres 42 Taman Ria, Manokwari Regency, West Papua Province, for the 2022/2023 Academic Year. This research is a School Action Research (PTS) with a qualitative descriptive approach. This study aims to analyze the professional competence of teachers from the aspect of mastery of material, concepts, structures, and scientific patterns that support subjects, mastery of competency standards and basic competencies and the ability to develop creatively taught learning materials. The data sources used are primary and secondary data. Primary data comes from interviews and class observations. Secondary data from observations of syllabus and lesson plans documents as well as other relevant documents. Data collection instruments used interview guides, observation sheets and documentation studies. Data analysis techniques used the Milles and Huberman model, namely data reduction, display and data verification. The results showed an increase in teacher professional competence after being supervised by the school principal, 68.18% (15 out of 22) succeeded in achieving the mastery indicator (? 80%) . There are 7 out of 22 teachers (31.82%) of whom are in the "Enough" category, which means that they still need further guidance specifically on aspects of developing creative learning materials. This shows that the implementation of academic supervision is able to improve the professional competence of teachers. The triggering factors for the low professional competence of teachers include 1) lack of self-motivation (self motivation); 2) low literacy skills; 3) difficulty getting out of the comfort zone; 4) having a narrow view of a change; 5) not optimally utilizing technology; 6) always think negatively; 7) self-closing; 8) lack of discipline. 9) do not feel ashamed to see other people busy working; 10) busy doing activities outside of school hours; 11) habit of procrastinating work. If routinely carried out, undoubtedly the teacher's supervisory competence will increase. Another effort that can be done is to involve teachers in various KKG activities, workshops, and IHT and even training organized by the government. In addition, giving motivation continues to be given to teachers so that they are motivated in carrying out their duties, including changing the teacher's paradigm so that they think positively about everything. ABSTRAKUpaya peningkatan Kompetensi Profesional Guru Melalui Implementasi Supervisi Akademik Kepala Sekolah telah dilaksanakan di SD Inpres 42 Taman Ria Kabupaten Manokwari Provinsi Papua Barat Tahun Ajaran 2022/2023. Penilitian ini adalah Penelitian Tindakan Sekolah (PTS) dengan pendekatan deskriptif kualitatif. Penelitian ini bertujuan untuk menganalisa kompetensi professional guru dari aspek penguasaan materi, konsep, struktur, dan pola keilmuan yang mendukung mata pelajaran, penguasaan standar kompetensi dan kompetensi dasar dan kemampuan mengebangkan materi pembelajaran yang diampu secara kreatif. Sumber data yang digunakan adalah data primer dan sekunder. Data primer bersumber dari hasil wawancara dan observasi kelas. Data sekunder dari observasi terhadap dokumen silabus dan RPP serta dokumen lain yang relevan.Instrumen pengumpulan data menggunakan pedoman wawancara, lembar observasi dan studi dokumentasi. Teknik analisis data menggunakan model Milles and Hubermen yakni reduksi data, display dan dan verifikasi data.Hasil penelitian menunjukkan peningkatan kompetensi profesioanl guru setelah disupervisi oleh kepala sekolah, terdapat 68,18% (15 dari 22) berhasil mencapai indicator ketuntasana (? 80%). Terdapat 7 dari 22 guru(31,82%) diantaranya berada pada kategori “Cukup” yang artinya masih perlu bimbingan lebih lanjut khusus aspek pemngembangan materi pembelajaran secara kreaatif. Hal ini menunjukkan bahwa implementasi supervise akademik mampu meningkatkan kompetensi professional guru. Adapun faktor pemicu rendahnya kompetensi professional guru diantaranya 1) kurangnya motivasi diri (self motivation);2) kemampuan literasi yang rendah;3) sulit keluar dari zona nyaman;4) memiliki pandangan yang sempit terhadap suatu perubahan; 5) kurang maksimal memanfaatkan teknologi;6) selalu berpikir negative;7) menutup diri;8)kurang displin.9) tidak merasa malu melihat orang lain sibuk bekerja;10) sibuk melakukan aktivitas diluar jam sekolah;11) kebiasaan menunda pekerjaan.Jika supervise rutin dilakukan niscaya kompetensi guru akan meningkat. Upaya lain yang dapat dilakukan adalah mengikutsertakan guru dalam berbagai kegiatan KKG,workshop, dan IHT bahkan pelatihan yang diselenggrakan oleh pemerintah. Selain itu pemberian motivasi terus diberikan kepada guru agar termotivasi dalam melakukan tugasnya termasuk mengubah paradigma guru sehingga berpikir positif terhadap segala hal.